2002
DOI: 10.1038/sj.npp.1300039
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effects of Haloperidol, Risperidone, and Clozapine Exposure on Cholinergic Markers and Spatial Learning Performance in Rats

Abstract: Haloperidol (HAL), a potent typical antipsychotic, continues to be a frequently prescribed medication for behavioral disturbances associated particularly with schizophrenia despite well-documented adverse effects associated with its chronic use. Animal experiments have even indicated that HAL can damage cholinergic pathways and thus could be especially deleterious to those experiencing cognitive deficits. However, several recent clinical studies indicate that atypical antipsychotics may actually improve cognit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
53
0

Year Published

2004
2004
2009
2009

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(60 citation statements)
references
References 37 publications
7
53
0
Order By: Relevance
“…Although a number of neuroleptic drugs (administered acutely) reverse or attenuate PPI deficits in pharmacological and neurodevelopmental models of schizophrenia (for review, see Geyer and Ellenbroek, 2003), the effects of chronic antipsychotic treatment (i.e., similar to the situation in schizophrenia) have not been evaluated. Several neurotransmitters, including dopamine, serotonin, and glutamate, are known to regulate PPI; however, observations that decreased cholinergic activity results in PPI disruption (Stanhope et al, 2001;Jones et al, 2005) were of particular interest to us in light of our previous findings of neuroleptic-associated decreases in ChAT (Terry et al, 2003). In the present study, neither HAL nor ZIP (i.e., in a normal, nonimpaired animal model) was associated with significant alterations in PPI or startle amplitude, even though these agents were associated with quite notable (negative) effects on cholinergic markers (see below).…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Although a number of neuroleptic drugs (administered acutely) reverse or attenuate PPI deficits in pharmacological and neurodevelopmental models of schizophrenia (for review, see Geyer and Ellenbroek, 2003), the effects of chronic antipsychotic treatment (i.e., similar to the situation in schizophrenia) have not been evaluated. Several neurotransmitters, including dopamine, serotonin, and glutamate, are known to regulate PPI; however, observations that decreased cholinergic activity results in PPI disruption (Stanhope et al, 2001;Jones et al, 2005) were of particular interest to us in light of our previous findings of neuroleptic-associated decreases in ChAT (Terry et al, 2003). In the present study, neither HAL nor ZIP (i.e., in a normal, nonimpaired animal model) was associated with significant alterations in PPI or startle amplitude, even though these agents were associated with quite notable (negative) effects on cholinergic markers (see below).…”
Section: Discussionmentioning
confidence: 91%
“…Oral antipsychotic dosing was based several factors: 1) for HAL, previous rodent studies in our laboratory in which time-dependent behavioral and neurochemical effects were detected and plasma drug levels were achieved that approximated those often associated with antipsychotic effects in humans (Terry et al, 2002(Terry et al, , 2003(Terry et al, , 2005a; and 2) for ZIP, previous studies using oral dosing in rodents in which notable behavioral effects were observed (Mansbach et al, 2001). Furthermore, for both HAL and ZIP, the doses selected (see below) would be expected to achieve comparable (and therapeutically) relevant D 2 receptor occupancy values in vivo (i.e., in the range 65-80%; see Kapur et al, 2003) based on the recent work of Barth et al (2006).…”
Section: Drug Dosing For Chronic Antipsychotic Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, haloperidol does not greatly restore cognitive performance, while the beneficial effects of clozapine and other multireceptorial antipsychotics are unremarkable; furthermore, it is unclear to what extent they represent a specific and primary affect upon mnemonic function (Woodward et al, 2005;Thornton et al, 2006). Experimental models of cognitive function have similarly revealed inconsistent effects of antipsychotics (Terry et al, 2003;Hagan and Jones, 2005;Hou et al, 2006). One reason underlying limited and variable efficacy is their potent antagonism of muscarinic, ␣ 1 -adrenergic, and histamine H 1 receptors, which compromises cognitive function (Bacciottini et al, 2001;Ito, 2004;Sarter et al, 2005).…”
mentioning
confidence: 99%
“…While some studies have reported that shortterm neuroleptic treatment in rodents (40-90 days) leads to decreases in ChAT activity and ChAT-immunostained neurons in several brain regions (Mahadik et al, 1988;Terry et al, 2003), long-term treatment (6-12 months) produces more variable results, including increases, decreases, or no significant effect on ChAT activity, ChAT-immunoreactive neurons, acetylcholine levels and other indices of cholinergic function (Grimm et al, 2001;Lohr et al, 2000;Mithani et al, 1987;Murugaiah et al, 1982;Rupniak et al, 1986;Terry et al, 2007). These discrepancies may be explained by region-specific effects (the decrease in ChAT+ cells being more prominent in ventral striatum and NA) (Grimm et al, 2001), length of administration and types of drugs used (typical neuroleptics being more likely to cause changes in cholinergic function than the atypical risperidone and clozapine) (Friedman et al, 1983;Terry et al, 2003). Recent studies have reported that the density of cholinergic neurons in the limbic striatum is decreased in patients with schizophrenia (Holt et al, 1999) and that the lowest density of ChAT+ neurons was found in two schizophrenic individuals that had not been treated with neuroleptics.…”
Section: Discussionmentioning
confidence: 99%